Analysis of Financial Technology and Financial Literacy on Business Development in MSMEs in the Village of Cawang East Jakarta - Pramadita, Anisa Bunga Putri; Siswantini, Tri (Formosa Journal of Sustainable Research, 2024)
This research is a quantitative descriptive study which aims to determine the influence of Financial Technology and Financial Literacy on Business Development in MSMEs in the village of Cawang, East Jakarta. This research uses MSMEs in the village of Cawang, East Jakarta as research samples. The sampling technique in this research used a probability sampling technique with a random sampling method so that the sample used was 100 MSME actors in the village of Cawang, East Jakarta. The hypothesis test used is Partial Least Square (PLS) with a significance level of 5% using the help of SmartPLS 4.0 software. The research results show that that (1) financial technology influences business development, (2) financial literacy does not influence business development